The Role of the Reflective Thinking Scale for International Students in China Through Factor Analysis - Jiangtao Fu; Ali Usman Hali (Behavioral Sciences)
Reflective thinking is crucial for academic success, personal development, and cultural adaptation. Therefore, this study aimed to analyze the role of the Reflective Thinking Scale (RTS) for international students in Chinese universities. Data were collected from 482 international students in Northwestern China. Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), Reliability, and Correlation Analysis were employed to validate the RTS. The qualitative phase used semi-structured interviews and reflective journals. The results revealed a four-factor structure for the RTS: habitual action, understanding, reflection, and critical reflection. The scale showed strong reliability (Cronbach’s α = 0.77) with significant positive correlations between reflective thinking and academic performance. The qualitative phase drew on 26 interviews and 22 reflective journals, analyzed thematically. Six themes emerged, highlighting reflection’s role in academic regulation, language acquisition, cultural adaptation, emotional processing, and personal identity development. The findings confirm the cross-cultural validity of the RTS and underscore the importance of scaffolded reflective practices in international education. This study also extends theoretical links between reflective thinking, transformative learning, cognitive flexibility, and self-regulated learning. Implications are offered for educators, curriculum designers, and researchers seeking to enhance reflective learning environments for diverse student populations.